First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species - Huerta, Heron (Zootaxa, 2018)
The first record of the family Bolitophilidae from Mexico is reported from the “Lagunas de Zempoala” Natural Reserve, situated between the borders of the states of Morelos and Mexico (included in the Nearctic Region), with a description and illustration of a new species, Bolitophila (Bolitophila) zempoala spec. nov., based on adults males collected with Malaise traps at an altitude of 2,841 m. a. s. l. in the Neo-Volcanic Axis mountains. The new species from Mexico is very closely related to Bolitophila (Bolitophila) dubiosa Van Duzee, 1928 and B. (B.) dupla Garrett, 1925.